Nilai Tinggi Tidak Menjamin Integritas Tinggi sebagai Cerminan Kegagalan Pendidikan Karakter dalam Realitas Indonesia Modern - Aliyah Arfiandini; Gladis Adelira Ardhana; Irma Ainur Rohmah; Alya Sausan Az Zahra (Jurnal Pendidikan dan Kewarganegara Indonesia, 2026)
This study aims to analyze the gap between academic achievement and student integrity as reflection of character education failures in modern Indonesian education. Using A literature synthesis methodology incorporating systematic identification, selection, data extraction, thematic synthesis, cross-study integration, and source triangulation, 20 academic references published between 2021 and 2026 were analyzed. Sources include nationally accredited journals, official government reports from the Corruption Eradication Commission (KPK) and Statistics Indonesia (BPS), and international publications. The findings confirm three core propositions: first, the paradox between academic value and integrity is empirically supported, as indicated by the National Education Integrity Index (IIP) of 69.5 in 2024 and the Anti-Corruption Behavior Index (IPAK) showing increased permissiveness toward corruption among higher-educated groups; second, character education failures are structural and systematic, stemming from overly cognitive-centered curricula, lack of teacher modeling, and weak school-family synergy; and third, digital modernity exacerbates the paradox through AI-based plagiarism and digital academic dishonesty. This study concludes that educational success cannot be measured solely through academic scores; integrity, responsibility, and honesty must become primary evaluation indicators to produce graduates who are not only intellectually capable but also morally grounded.